VALIDITAS KIT PRAKTIKUM DESTILASI SEDERHANA BERBASIS LINGKUNGAN PADA MATERI PEMISAHAN CAMPURAN KELAS VII DI SMP/MTS SUNGAI RAYA - Purwanto, Sandi; Masriani, Masriani; Rasmawan, Rahmat; Hairida, Hairida; Hadi, Lukman (Jurnal Kajian Pembelajaran dan Keilmuan, 2022)
The purpose of this study was to determine the feasibility of the practicum KIT and the teacher's response to the media developed in the environment-based simple distillation practicum KIT for class VII at SMP/Mts Sungai Raya. The instrument used in this study to collect data was questionnaire. Based on the results of the feasibility assessment of the media, this simple distillation practicum KIT was easy to use in distillation practicum with the lowest score of 83.3% with very good criteria. Meanwhile, the highest score percentage is 100% with very good criteria, stated in statements 1, 2 and 5. The highest score percentage   showed that the environment-based simple distillation practicum KIT media really referred to the mixture separation material. Teacher commented that the practicum KIT helped carry out learning efficiently. Based on the recapitulation of the teachers"™ responses on questionnaire, the average score obtained was 93.29% with very good criteria.